2014
DOI: 10.1177/0021998314541490
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and properties of functionally graded Al/AlB2 composites

Abstract: In the present study, an AlB 2 -reinforced functionally graded aluminium matrix composite has been produced by centrifugal casting. Boron 1.2-1.85% by weight has been dissolved in aluminium at 1400 C by adding boron oxide resulting in AlB 2 flakes 2.71-4.20% by weight before being cast centrifugally at 800 C. Results showed that there were two distinct regions without a smooth grading: one is rich of AlB 2 and the other is poor of AlB 2 . The highest AlB 2 content has been found to be around 11% in outer zones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…In a study, Ramadan and Omer fabricated FGAACs of varying fraction volumes of boron (1.2% to 1.85% wt), dispersed in Al, Al-Cu, and Al-Si alloys matrixes respectively, using CCT [56]. It was observed that B could only dissolve in aluminium alloys sufficiently at elevated tempera- [56].…”
Section: Application Of Cctmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study, Ramadan and Omer fabricated FGAACs of varying fraction volumes of boron (1.2% to 1.85% wt), dispersed in Al, Al-Cu, and Al-Si alloys matrixes respectively, using CCT [56]. It was observed that B could only dissolve in aluminium alloys sufficiently at elevated tempera- [56].…”
Section: Application Of Cctmentioning
confidence: 99%
“…It was observed that B could only dissolve in aluminium alloys sufficiently at elevated tempera- [56].…”
Section: Application Of Cctmentioning
confidence: 99%
“…Commercial Al-B master alloys are used as boron donors in the production of AlB 2 composites [8,9]. Commercial Al-B alloys are widely used as grain refiners in the casting of aluminum alloys and in the production of high conductivity conductor wire [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…3,5 This technique can be used to obtain a linear concentration gradient of reinforcement for any composition of the reinforcement and matrix materials, provided there is a difference in their density. A method which also uses the difference in the density of materials is centrifugal casting, 6 which allows obtaining, depending on the orientation of the mould relative to the rotation axis, both linear gradient, 7,8 as well as radial gradient, [9][10][11] which is useful in such applications such as engine or compressor pistons, bearings elements. If the difference in the density of the material and the matrix is insufficient to achieve due to the action of gravity or the centrifugal force of the concentration gradient in the desired direction, other physical phenomena can be used (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Figure10. Division of the sleeve section into areas, used in the analysis of reinforcement fraction and bands, marked in grey, was taken into account when calculating the Feret diameter of particles.…”
mentioning
confidence: 99%